Yurisprudensi MA No.1/Yur/Ag/2018 Tentang Pemberian Wasiat Wajibah Kepada Ahli Waris Non Muslim Perspektif Hukum Islam (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2023)
Al-Qur'an, Hadith, and KHI have determined that religious differences are a barrier to inheritance. Along with the development of the era, the phenomenon of religious differences between heirs and heirs is increasingly found, so it is necessary to have a permanent law that regulates it. Therefore, the Supreme Court established Supreme Court Jurisprudence Number 1/Yur/Ag of 2018 concerning the granting of obligatory wills to non-Muslim heirs. On the other hand, if this law is not examined more deeply, it will seem to be at odds with the regulations in Islamic inheritance law. The purpose of this study is to analyze the Supreme Court Jurisprudence Number 1/Yur/Ag of 2018 from the perspective of Islamic fiqh law. Researchers used a qualitative approach with normative Islamic law research methods, namely legal clinical and data collection methods, namely literature studies and processed using content analysis methods. The result of this research is MA Juridprudence No. 1/Yur/Ag 2018 does not conflict with Islamic inheritance law because these non-Muslims do not become heirs but receive a mandatory will because a mandatory will can be given to anyone regardless of their religion